Stages in Development and Changes in Human Resources of Dakwah Institutions in Palembang Community - Aswari, Nuha Nabila; Firdaus, Muhammad; Castrawijaya, Cecep (Jurnal Kajian Manajemen Dakwah, 2024)
This research aims to find out about the challenges of fa’wah institutions and changes in human resources that occur in Palembang. The research method using a qualitative approach. Data was collected through literature study and observation. This research was carried out by looking at the Palembang community environment. The results of the research show that the stage of development of human resources in Palembang community da’wah institutions has experienced significant changes from time to time. This changes is influenced by internal and exterbnal factors, such as changes in organizational policies, socio cultural dynamics and sociental demands. Human resources in da’wah institutions have increased in quality and quantity through various training and development programs organized by these institutions. However, there are still several obstacles that hinder the process of developing human resources, such as limited funds and lack of awareness of the importance of self development. Therefore, further efforts are needed to improve the role and quality of human resources in Palembang community da’wah institutions in order to face increasingly relevant challenges in the future.